Challenges and opportunities for cyber norms in ASEAN. Issue 2 (4th May 2018) - Tran Dai, Candice; Gomez, Miguel Alberto
ABSTRACT: The growing frequency of state-associated cyberattacks has led to calls for the establishment of rules of behaviour in this increasingly relevant domain. While there has been no shortage of such initiatives over the past decade, their respective outcomes have highlighted the unique challenges faced by norm entrepreneurs in cyberspace. Questions of the contrasting conceptualizations of cyberspace and varying threat perceptions have stymied attempts to establish a globally acceptable set of norms that regulate state behaviour. As the Association of Southeast Asian Nations (ASEAN) continues to invest heavily in this domain, calls for the creation of cyber norms within the region have been made. Yet despite this positive development, this paper illustrates that the unique characteristics of ASEAN pose significant obstacles to the emergence and eventual internalisation of cyber norms. In response, this paper argues that success in this endeavour requires initiatives that focus on confidence and capacity-building measures to mitigate these constraints. Although the likelihood of common norms across ASEAN remains uncertain, the approach suggested may lead to the emergence of different yet congruent norms within the bloc.